ANALYSIS OF SWATH CONFIGURATION IN PICKING-UP ZONE DEPENDING ON PICKER KINEMATIC PERFORMANCE - Olga N. Lesnyak; Stanislav M. Krasnostup; Anatoly D. Azarov (Advanced Engineering Research, 2012)
The swath model in the form of the catenary curve is described . The dependence of the swath configuration on the technological process of t he belt conveyer picker is analyzed.